(untitled) (Medico Legal Update, 2020)
A prospective study on 142 patients presenting with (benign euthyroid nodule) , after diagnostic work-up included a clinical evaluation, thyroid function tests, ultrasonography, thyroid scintigraphy and fine needle aspiration cytology. Based on the investigations, patients were managed with aspiration andthyroxine suppression therapy for sex month . Patients were divided into four groups according to their response of treatment ,group( 1) complete shrinkage response ,group( 2) reduction in size ,group (3) no response but same size and group (4) enlarge in size non responders’.Of the 142 patients17 (12 %) were male, and 125 (88 %) were female. The age rangein 99 (69.7%) patients were between 21 and 50 years and forty three patients were above 50 years of age. We divided our result into four groups,group( 1) complete shrinkage response29 patients’ (20.5%),group( 2) reduction in size 45 patients’ (31.8%),group (3) no response but same size38 patients’ (26.7%) and group (4) enlarge in size non responders30 patients’(21% )Thyroxine suppressive treatment were effective in shrinking about one fifth of thyroid nodules. Similarly, there was reduction in size in about one third of nodule.From 17 male 6 patients (35 %) achieve complete response ,while only23 female patients (18 %) achieve complete response, and from17 male patients 5 (29 %) achievereduction in size,while only 40 female patients (32 %) achieve reduction in size. Young age less than fifty achieve good response than older patients(63.6%).Single aspiration needed in26 patients(18.3%) while multiple aspiration needed in 116 patients(81.7%).